2001
DOI: 10.1179/joc.2001.13.supplement-2.159
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Induced Endotoxin Release and Clinical Sepsis: a Review

Abstract: Sepsis and peritonitis have not lost much of their danger for patients. The mortality rate in peritonitis has only marginally decreased during the last 30 years despite aggressive surgical and sophisticated intensive care treatment. In intra-abdominal infection and peritonitis source control remains the mainstay of treatment, although general principles and denominators of successful source control need to be established. Endotoxin has been recognized as a major player in the pathogenesis of sepsis and its sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 93 publications
2
74
0
1
Order By: Relevance
“…Several other investigators had reported elevated levels of TNF-␣ in the presence of TNF-␣Ϫ308, TNF-␣Ϫ238, and LT-␣ϩ250 alleles (22,40,41). However, several intrapartum events, such as fetal distress, maternal fever, and/or intrapartum administration of antibiotics, may affect cord blood TNF-␣ levels (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Several other investigators had reported elevated levels of TNF-␣ in the presence of TNF-␣Ϫ308, TNF-␣Ϫ238, and LT-␣ϩ250 alleles (22,40,41). However, several intrapartum events, such as fetal distress, maternal fever, and/or intrapartum administration of antibiotics, may affect cord blood TNF-␣ levels (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this are several fold and include issues related to participant selection and antibiotic efficacy, tissue biodistribution and microbial resistance (Keelan 2011). In addition, bactericidal antibiotics cause bacterial lysis and release of endotoxins, further activating the innate immune system and promoting the release of prostaglandins that may actually stimulate the onset of labour (Dofferhoff et al 1991, Hurley 1995, Holzheimer 2001). …”
Section: Introductionmentioning
confidence: 99%
“…LPS can be released from dying bacteria either through the action of the body's natural defense system or due to the administration of antibiotics (10,21). Upon cellular recognition of LPS, inflammatory mediators are produced which may lead to serious physiological damage ranging from hypotension or disseminated vascular coagulation to multiple organ failure (3,29).…”
mentioning
confidence: 99%